Efficiency and frontier technology in the aftermath of recessions: International evidence - Dimitris Christopoulos; Miguel León-Ledesma (University of Kent, School of Economics, 2009)
The relationship between recessions and productivity has been the focus of an important body of theoretical and empirical research in the last two decades. We contribute to this literature by presenting new evidence on the evolution of productivity in the aftermath of recessions. Our method allows us to distinguish between frontier technology and (in-)efficiency effects of recessions. We present international evidence for a panel of 70 countries for the 1960-2000 period. Our results reveal that the average cumulative impact of recessions on productivity up to four years after its end is negative and signifcant. This, however, results from a mixture of mechanisms. The level of frontier productivity increases, but the rate of technical progress decreases, leading to a fall in frontier productivity. Efficiency also falls, lending support for the idea that recessions tend to reduce, rather than increase, economic restructuring. Long and deep recessions are also shown to have distinctive impacts on productivity.
Keywords: F31; F37; C32; 330; growth and cycles; recessions; technical effciency; technical progress; Wirtschaftswachstum; Produktivität; Konjunktur; Technische Effizienz; Technischer Fortschritt; Theorie